Analysis and exploration of critical success factors : business intelligence success in malaysia organization Kuala Lumpur - Muhammad Asyraf bin Rodzoan (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2018)
This investigation seeks to use the base of knowledge and empirically test the relationship between the segments of authoritative organization culture and information management practice towards implementing the daily business operations. The study adopted the exploratory research approach to explore the impact. To implement the integrated information system, centralising and automating are the most essential controls in an organisation, namely those with hierarchical structure due to its overall diverse business process. This study examined the leverage of technology in achieving the highest quality standards and operational efficiency through speedy information delivery via one integrated system to improve sharing of information across departmental and levels. Thus, it seeks to determine whether the application has been able to improve the timeliness of business information update from diverse locations and improve the accuracy of information capture, the quality of information processing and reporting and also the setting up of key performance measures for the company's operational levels.